A Novel and Alternative Treatment Method for Diabetic Heel Ulceration Exposing the Calcaneus Which Is Not Suitable for Flap Surgery: Vacuum Assisted Sandwich Dermal Matrix. (21st September 2015) - Bingol, Ugur A.; Cinar, Can; Arslan, Hakan; Altındas, Muzaffer
Abstract : Background . Currently, free flaps and pedicled flaps are the first treatment choices for large heel ulcer reconstruction. However, flap reconstruction of heel ulcerations cannot be performed in all diabetics especially with concurrent severe peripheral vascular disease because of higher flap failure rate. In recent years, the use of acellular dermal matrix (ADM) has emerged as an alternative treatment option for extremity ulcers. Methods . We present 13 diabetic patients with a large heel ulceration exposing the calcaneus, who were not eligible for flap surgery due to the presence of only one patent artery of trifurcation. These cases were treated with the vacuum assisted sandwich dermal matrix (VASDEM) method. Results . None of the patients required amputation. Skin grafting was successful in ten patients. Although partial losses were observed in three patients, they were healed spontaneously without surgical interventions. During the follow-up period none of the patients developed ulceration on the treatment area. All patients maintained their preoperative ambulatory ability. Conclusion . VASDEM is a novel method offering opportunity for treatment before proceeding to amputation in diabetic heel ulceration exposing the calcaneus which is not suitable for flap surgery. It also has the potential to close wounds of all sizes independent of the vessel status and wound size in selected diabetic patients.